Variasi beban terhadap performansi mesin otto menggunakan rem cakram: Skala Laboratorium - Siregar, Zufri Hasrudy; Ramadhan, Andri; Silaban, Donni; Refiza, Refiza (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2024)
Also known as the most commonly used gasoline engine, disc brakes are an important component of the Otto engine's braking system that can affect the safety and efficiency of the vehicle. This study aims to analyze the variation of load on the performance of Otto machines using disc brakes on a laboratory scale where most of the research was carried out in less representative environments, such as computer simulations or complex field testing. The lack of studies on a laboratory scale that carefully account for load variations leaves a significant knowledge gap. The test parameters are the calculation of torque, power and Break Mean Effective Pressure (BMEP). From this study, it was found that at a load of 0.125 kg the lowest torque was 0.24525 N.m and the highest torque was 0.82404 N.m at a load of 0.420 kg. Then with a load of 0.125 kg the lowest power output is 0.64173 N.m and the highest power at a load of 0.420 kg is 2.15623 KW. Bmeep will increase when the load applied is greater at 0.125 kg resulting in the lowest bmeep being 2.78287 N.m and the highest bmeep at 0.420 kg load is 9.35052 N.m